2020
DOI: 10.3390/cancers12102796
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Residential Altitude on the Molecular Profile and Survival of Melanoma: Results of an Interreg Study

Abstract: Cutaneous melanoma (CM) incidence is rising worldwide and is the primary cause of death from skin disease in the Western world. Personal risk factors linked to environmental ultraviolet radiation (UVR) are well-known etiological factors contributing to its development. Nevertheless, UVR can contribute to the development of CM in different patterns and to varying degrees. The present study aimed at investigating whether altitude of residence can contribute to the development of specific types of CM and/or influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In terms of UV exposure, TYRP1 (tyrosinase-related protein 1) and miR-204-5p (a member of the miRNA family; it is down-regulated and functions as a tumor suppressor in various types of human tumors) were highly expressed in patients with cutaneous melanoma living at higher altitudes [39]. Finally, we must not forget the C-KIT gene mutation that is retrieved in 11% of patients with melanoma.…”
Section: Gene Mutations In Melanomamentioning
confidence: 99%
“…In terms of UV exposure, TYRP1 (tyrosinase-related protein 1) and miR-204-5p (a member of the miRNA family; it is down-regulated and functions as a tumor suppressor in various types of human tumors) were highly expressed in patients with cutaneous melanoma living at higher altitudes [39]. Finally, we must not forget the C-KIT gene mutation that is retrieved in 11% of patients with melanoma.…”
Section: Gene Mutations In Melanomamentioning
confidence: 99%
“…MiR-211-5p was first identified as a diagnostic biomarker of melanoma [ 8 ]. With the deepening of researches on miR-211-5p, other biological functions had been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies demonstrated that miR-211-5p had therapeutic functions on melanoma and other tumors [8][9][10]. Mature miRNA is assembled into the RNA-induced silencing complex (RISC), which recognizes the 3 UTR region of target gene mRNA by complementary base pairing, and guides the RISC to degrade the target mRNA or block the mRNA translation, thereby negatively regulating the expression of the target gene [11].…”
Section: Introductionmentioning
confidence: 99%
“…In osteoarthritis, miR-211-5p contributed to chondrocyte differentiation by suppressing Fibulin-4 expression (35,36). Several previous studies showed that mir-211-5p was also associated with many types of cancer, including renal cancer, hepatocellular carcinoma, breast cancer, and malignant melanoma (37)(38)(39)(40)(41)(42)(43). SMOC1 is a protein-coding gene that may play an important role in ocular development (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%